Evaluation of Entre-os-Rios Thermal Aquifer Vulnerability Using DRASTIC Index - Gonçalves, Vanessa; Albuquerque, António; Cavaleiro, Victor (KnE Materials Science, 2022)
The “Entre-os-Rios” thermal aquifer has a protection perimeter buffer zone for avoiding water contamination. A vulnerability map was generated, using geographic information systems (GIS) tools and the DRASTIC index, to evaluate the risk of contamination of the perimeter area. The results showed that the protection perimeter buffer zone has an insignificant to moderate risk of pollution, with the DRASTIC index’s values ranging from 47 to 127 points, and an average pollution vulnerability of 79 points. The alluvium-covered land is vulnerable to moderate contamination but is located far from the catchment point. Areas of minimal risk correspond to locations where the granitic massif has not been altered significantly. Keywords: geographic information systems, vulnerability map, protection perimeter buffer zone, DRASTIC index